2020
DOI: 10.1097/tp.0000000000003376
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Organ, Tissue, and Vascularized Composite Allograft (VCA) Donation and Transplantation: A Survey of United States Military Veterans

Abstract: Original Clinical Science-GeneralBackground. There are 20 million living US armed forces veterans; however, the organ donation attitudes of veterans have not been examined. Methods. Over a 17-month period, a convenience sample of 1517 veterans in New England completed a survey to assess attitudes about organ, tissue, and vascularized composite allograft (VCA) donation. Results. Most veterans (96%) supported the donation of organs and tissue for transplantation, and 59% were registered as an organ and tissue do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 42 publications
(61 reference statements)
1
10
0
Order By: Relevance
“… 13 A survey of the general public in 2016 (N = 1485) found that two-thirds of respondents were willing to donate their own face, legs, and hands/forearms, with a majority also expressing willingness to donate the penis and uterus. 14 Similar levels of support for VCA donation were found among veterans 15 and the general public when asked about a VCA donation from a deceased family member whose donation wishes were known. 14 A recent Gallup poll found strong support for solid organ donation (90.4%) but drastically lower support for VCA donation; 64% of respondents were willing to donate their own hands and 46.9% were willing to donate their own face after death.…”
Section: Introductionmentioning
confidence: 67%
“… 13 A survey of the general public in 2016 (N = 1485) found that two-thirds of respondents were willing to donate their own face, legs, and hands/forearms, with a majority also expressing willingness to donate the penis and uterus. 14 Similar levels of support for VCA donation were found among veterans 15 and the general public when asked about a VCA donation from a deceased family member whose donation wishes were known. 14 A recent Gallup poll found strong support for solid organ donation (90.4%) but drastically lower support for VCA donation; 64% of respondents were willing to donate their own hands and 46.9% were willing to donate their own face after death.…”
Section: Introductionmentioning
confidence: 67%
“…Indeed, veterans may have more favorable attitudes toward both traditional and VCA organ donation compared with the general population. 14,20 Video messaging is an effective and persuasive strategy for increasing favorable attitudes toward organ donation and donor registry enrollment. 22,[31][32][33] We extend these findings by showing that video messaging is also effective at increasing behavioral willingness to donate VCA organs.…”
Section: Discussionmentioning
confidence: 99%
“…First, a survey of veterans was done to assess VCA attitudes and to identify knowledge gaps. 20 Second, 6 focus groups of 43 veterans were held in 4…”
Section: Video Intervention: Donation Messagingmentioning
confidence: 99%
See 1 more Smart Citation
“…14 While veterans have been described as having high interest in donation, recovery of donors at Veteran Administration Medical Centers (VAMCs) is a rare occurence. 15 In this report, we describe historical organ donation performance and access to organ donation care for United States military veterans receiving care at VAMCs.…”
mentioning
confidence: 99%